Правове дослідження прецедентів встановлення статусу історичних вод в Арктиці - Аверочкіна, Тетяна Володимирівна; Аверочкина, Татьяна Владимировна; Averochkіna, T. (My University, 2011)
In article it is considered practice of the states concerning an establish- ment of the status of historical waters in Arctic regions. The author notices, that for internal sea waters of the subpolar countries the establishment them concerning some sea spaces of the status of historical waters on the basis of the general norms of the international marine law ﬁ xed in the Convention on the territorial sea and a contiguous zone of 1958 and the Convention of the United Nations on a marine law of 1982, and also the national legislation is charac- teristic. Practice of the Russian Federation, Norway and Canada concerning an establishment in coastal sea strips of Arctic ocean of a mode of historical waters is considered.
Аверочкіна Т. В. Правове дослідження прецедентів встановлення статусу історичних вод в Арктиці / Т. В. Аверочкіна // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред.), Л. І. Кормич (заст. голов. ред.), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України, НУ ОЮА. – Одеса : Фенікс, 2011. – Вип. 42. – С. 159 - 165.
Keywords: дослідження прецедентів; исследования прецедентов; історичні води в Арктиці; исторические воды в Арктике; historic waters in the Arctic; research precedents; внутрішні морські води; Конвенція ООН по морському праву; internal sea waters; внутренние воды; Конвенция ООН по морскому праву; United Nations Convention on the Law of the Sea